Health Care System for Alzuhaimer Patient Using Arduino - Ismael, Ali Saber Maki; Hussin, Zainab Haidar Samawi; Abdulkarim, Nidal Omar Muwaffaq; Marza, Karim Hussein Obaid (American Journal of Botany and Bioengineering, 2024)
We have recently noticed an increase in Alzheimer’s disease in the elderly, especially the elderly This has led to companies competing to help people afflicted with this disease So in this project a system was designed to help patients with Alzheimer’s disease. This project aims to design a watch that contains some sensors to monitor the patient’s status such as position by using GPS sensor, in addition to some sensor use to monitering any suddenly events by gyroscope sensor such as Direct fall or fainting. These data are send to monitoring person or center to tell the emergency in case event any thing.